Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1109/tnsre.2017.2692520
|View full text |Cite
|
Sign up to set email alerts
|

Portable and Reconfigurable Wrist Robot Improves Hand Function for Post-Stroke Subjects

Abstract: Rehabilitation robots have become increasingly popular for stroke rehabilitation. However, the high cost of robots hampers their implementation on a large scale. This paper implements the concept of a modular and reconfigurable robot, reducing its cost and size by adopting different therapeutic end effectors for different training movements using a single robot. The challenge is to increase the robot's portability and identify appropriate kinds of modular tools and configurations. Because literature on the eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 50 publications
0
26
0
1
Order By: Relevance
“…From this study, visual biofeedback about the quality and quantity of wrist movements was attained, which resulted in improvements in ARAT scores. In a more recent study, Khor et al [46] discussed the improvements in a 30 min, robot-assisted study for 7 participants who actively took part in clinical and home-based rehab therapy, and who showed improvements in both hand and arm functions. This therapy was assisted by the CR2-Haptic device alongside a VR game, and it was reported that all subjects were comfortable with the therapy.…”
Section: Discussionmentioning
confidence: 99%
“…From this study, visual biofeedback about the quality and quantity of wrist movements was attained, which resulted in improvements in ARAT scores. In a more recent study, Khor et al [46] discussed the improvements in a 30 min, robot-assisted study for 7 participants who actively took part in clinical and home-based rehab therapy, and who showed improvements in both hand and arm functions. This therapy was assisted by the CR2-Haptic device alongside a VR game, and it was reported that all subjects were comfortable with the therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Comparado ao treino manual do braço, o treino suportado por robô pode ser mais intensivo, de maior duração e mais repetitivo, conferindo aos robôs o potencial de melhorar o processo de reabilitação em pacientes com AVC (13) . No entanto, o custo dos robôs de reabilitação ainda é um problema, limitando o seu perfil de custo-benefício e dificultando a avaliação e implementação em larga escala 14 . Os dispositivos hápticos, identificados num elevado número de artigos com o objetivo de potenciar a função do membro afetado, podem exercer o movimento de forma passiva, ativa assistida ou resistida, com a possibilidade de transmitirem um feedback a vários níveis, desde vibrotátil, visual, auditivo ou mesmo propriocetivo.…”
Section: Irex®unclassified
“…The reconfigurable nature of the system allows for different movements to be trained with a single system. A clinical study showed that the CR2-Haptic resulted in improved forearm pronation-supination and wrist flexion-extension after 6 weeks of training (Khor et al 2017). Like the InMotion and Armeo Power systems, the CR2-Haptic is designed to be used in a clinical setting, but it is much more affordable while providing many of the same features.…”
Section: End-effector Therapy Robotsmentioning
confidence: 99%